Soil – Environment – Sustainability - Várallyay, György (Acta Agraria Debreceniensis, 2012)
The future and life quality of human society depends primarily on the success of the sustainable use of natural resources: the geological strata–soil–water–biota–near surface atmosphere continuum. Soil is the most significant conditionally renewable natural resource in our Earth’s system, with three unique properties: multifunctionality; fertility/ productivity; resilience. In the case of rational land use and precise soil management soil does not disappear, and its desirable „quality” does not decrease considerably, irreversibly and unavoidably. Its renewal, however, requires continuous care and permanent activities.Consequently, the prevention, elimination or moderation of soil degradation processes and extreme hydrological situations (the two main factors limiting desirable soil multifunctionality) with rational land use and soil management are the key factors and priority tasks of sustainable development on each level and in each phase of the decisionmaking process.